Chemical, computational and functional insights into the chemical stability of the Hedgehog pathway inhibitor GANT61. (1st January 2018) - Calcaterra, Andrea; Iovine, Valentina; Botta, Bruno; Quaglio, Deborah; D'Acquarica, Ilaria; Ciogli, Alessia; Iazzetti, Antonia; Alfonsi, Romina; Lospinoso Severini, Ludovica; Infante, Paola; Di Marcotullio, Lucia; Mori, Mattia; et al.
Abstract: This work aims at elucidating the mechanism and kinetics of hydrolysis of GANT61, the first and most-widely used inhibitor of the Hedgehog (Hh) signalling pathway that targets Glioma-associated oncogene homologue (Gli) proteins, and at confirming the chemical nature of its bioactive form. GANT61 is poorly stable under physiological conditions and rapidly hydrolyses into an aldehyde species (GANT61-A), which is devoid of the biological activity against Hh signalling, and a diamine derivative (GANT61-D), which has shown inhibition of Gli-mediated transcription. Here, we combined chemical synthesis, NMR spectroscopy, analytical studies, molecular modelling and functional cell assays to characterise the GANT61 hydrolysis pathway. Our results show that GANT61-D is the bioactive form of GANT61 in NIH3T3 Shh-Light II cells and SuFu −/− mouse embryonic fibroblasts, and clarify the structural requirements for GANT61-D binding to Gli1. This study paves the way to the design of GANT61 derivatives with improved potency and chemical stability. Graphical Abstract: